Effect of cation size on electrochemical properties of polymer electrolyte - Jawad, Mohammed kadhim (Iraqi Journal of Physics, 2019)
This study investigates the ionic conduction dependence on the size of alkaline cations in gel polymer electrolytes based on double iodide can enhance by incorporating a salt having a bulky cation. Group of gel polymer electrolytes with polyethylene oxide (PEO) as a host matrix based on double salts potassium iodide (KI) and rubidium iodide (RbI) with different weight ratio prepared by using solution cast technique. The maximum value of conductivity reaches (6.03 10⁻3 at 293 K) S/cm for an electrolyte which content (KI 45%, RbI 5%) from binary salt. The ionic conductivity of for gel polymer electrolytes gradually increases by increasing temperature. The real dielectric constant results confirm that the dielectric behavior of the PEO material is a thermally activated process. FTIR results confirm that the shifting of peaks is another way to prove the interactions between PEO and binary salt ascribed to the formation of a transient cross-linking complex between the cations of the ionic liquids and the ether oxygen of the PEO.